(3efjI GddHjH aj TQM GdJgPjHs - (3GdCYQLj, YejO GdOjf Hf YHO GdeWdHs ((3ESeGYjd Hf MGLj Ydj GdgRGQLQjHjs)
(3ChdgG (B:s
(3Gddge Efj CMeOc MeO dG jbOQ MUQg(B... (3hjYO aEf GddGJaGJ Edi Yde CUhd Gdabg(B...s
(3BNQgG (B:s
(3hGdeYGQVI aj GdCUd hGdeYGQVI aj GdaQY hbO YQaJg hHGbj GdGYJQGVGJ hCLhHJgG JbOeJ(B. (3hMjK GfJgi GdcdGe(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3SfI(B1308(3g`s
Keywords: (3CUhd Gdabgs